GIS-BASED ANALYSIS OF SENIOR AND VOCATIONAL HIGH SCHOOL DISTRIBUTION PATTERNS IN KEPULAUAN YAPEN REGENCY - Muhammad Nurul Huda; Rafi Sulthan Rizqullah; Shalsabilla Aulia Putri; Nisrina Gina Rahma; Nasywa Cinta Az Zahrah; Nur Kahfi Mukhlisin Anwar (PT. Intelek Cendikiawan Nusantara, 2026)
This study examines how Senior High Schools (SMA) and Vocational High Schools (SMK) are distributed across Kepulauan Yapen Regency using Geographic Information Systems (GIS). School location data were taken from the Ministry of Education and verified through Google Maps, while administrative maps were obtained from the Geospatial Information Agency (BIG). Spatial analysis was carried out in ArcGIS Pro using the Average Nearest Neighbor (ANN), Mean Center, Standard Distance, and Standard Deviational Ellipse tools. The results show that the observed mean distance between schools is smaller than the expected mean distance, with a nearest-neighbor ratio of 0.779877, a z-score of −1.975184, and a p-value of 0.048247. These figures indicate that the distribution pattern is clustered at the 95% confidence level. The analysis also shows that most schools are concentrated along the southern coastal area, particularly around Serui in Yapen Selatan District, while the northern and outer island areas have fewer facilities and wider spacing between them. This shows that students in remote areas face relatively limited access to upper secondary education.